DNA damage response of clinical carbon ion versus photon radiation in human glioblastoma cells - Lopez Perez, Ramon; Schmezer, Peter (Radiotherapy and oncology, 2019)
Background and purpose - Carbon ion radiotherapy is a promising therapeutic option for glioblastoma patients due to its high physical dose conformity and greater biological effectiveness than photons. However, the biological effects of carbon ion radiation are still incompletely understood. Here, we systematically compared the biological effects of clinically used carbon ion radiation to photon radiation with emphasis on DNA repair. - Materials and methods - Two human glioblastoma cell lines (U87 and LN229) were irradiated with carbon ions or photons and DNA damage response was systematically analyzed, including clonogenic survival, induction and repair of DNA double-strand breaks (DSBs), cell cycle arrest and apoptosis or autophagy. γH2AX foci were analyzed by flow cytometry, conventional light microscopy and 3D superresolution microscopy. - Results - DSBs were repaired delayed and with slower kinetics after carbon ions versus photons. Carbon ions caused stronger and longer-lasting cell cycle delays, predominantly in G2 phase, and a higher rate of apoptosis. Compared to photons, the effectiveness of carbon ions was less cell cycle-dependent. Homologous recombination (HR) appeared to be more important for DSB repair after carbon ions versus photons in phosphatase and tensin homolog (PTEN)-deficient U87 cells, as opposed to PTEN-proficient LN229 cells. - Conclusion - Carbon ions induced more severe DSB damage than photons, which was repaired less efficiently in both cell lines. Thus, carbon ion radiotherapy may help to overcome resistance mechanisms of glioblastoma associated with DNA repair for example in combination with repair pathway-specific drugs in the context of personalized radiotherapy.